A New Algorithm to Encryption and Compression Image Data File - Riyad Mubarak Abdullah (College of Education for Pure Sciences, 2011)
ABSTRACT In this research algorithm to encryption and image compression data file was developed. This algorithm is a result of merge between RSA algorithm for encryption and Morlet Wavelet which is used for image data file compression. We applied this algorithm to a group of images which is randomly choused and bmp type with different in size and content, this algorithm gives good results for keeping the security of the information because the data file encrypted at the beginning and then compressed as a result it will be difficult to recognize the file content for unauthorized person.